Limit of Detection (LOD) of in-house N1N2 CDC real-time RT-PCR assay and commercial kits to detect SARS-CoV-2 - Simon Yosonegoro Liem; Fera Ibrahim; Andi Yasmon (Journal of Clinical Microbiology and Infectious Diseases, 2022)
Introduction: There are two types of SARS-CoV-2 real-time RT-PCR (rRT-PCR) kits used in the laboratory in Indonesia, in-house and commercial kits. Our laboratory developed an in-house kit based on N1N2 CDC. In this study, we reported the In-house kit's Limit of Detection (LOD) compared with several commercial kits. Method: This report was an experimental study conducted in Clinical Microbiology Laboratory, Microbiology Department, FMUI in Jakarta. Commercial SARS-CoV-2 RNA (Vircell, Granada, Spain, Lot No. 20MBC137004-R) was used. The LoD was determined using a 2-fold dilution of the RNA in DNase/RNase-free water (Vircell®). The diluted RNA(s) were used as templates for in-house and commercial rRT-PCR kits.  Result: The LOD of in-house rRT-PCR and three commercial kits (BioCoV-19 [Bio Farma], Standard M [SD Biosensor], and Real-Q [BioSewoom]) showed higher sensitivity (3.5 copies/reaction) than Power Chek [Kogenebiotech] (7 copies/reaction).  Conclusion: The LOD of our In-house kit showed high performance in sensitivity and comparable with other commercial kit.